Chemistry, properties, and applications of fluorographene - Chronopoulos, Demetrios D; Bakandritsos, Aristides; Pykal, Martin; Zbořil, Radek; Otyepka, Michal (Applied materials today, 2017)
Fluorographene, formally a two-dimensional stoichiometric graphene derivative, attracted remarkable attention of the scientific community due to its extraordinary physical and chemical properties. We overview the strategies for the preparation of fluorinated graphene derivatives, based on top-down and bottom-up approaches. The physical and chemical properties of fluorographene, which is considered as one of the thinnest insulators with a wide electronic band gap, are presented. Special attention is paid to the rapidly developing chemistry of fluorographene, which was advanced in the last few years. The unusually high reactivity of fluorographene, which can be chemically considered perfluorinated hydrocarbon, enables facile and scalable access to a wide portfolio of graphene derivatives, such as graphene acid, cyanographene and allyl-graphene. Finally, we summarize the so far reported applications of fluorographene and fluorinated graphenes, spanning from sensing and bioimaging to separation, electronics and energy technologies.
Keywords: Covalent functionalization; Fluorographene; Graphene derivatives; Chemistry